(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This research aims to reveal the concept of poetic imagery, its types and levels according to the blind poet Ali al-Husri al-Qayrawani in his collection entitled “The Suggestion of the Wounded and the Injury of the Wounded,” which he devoted entirely to the lamentation of his son Abd al-Ghani. We discussed the development of the concept of imagery among ancient and modern critics, and then shed light on the types of imagery. Image and its connection to the five senses (visual, auditory, tactile, gustatory, and olfactory). Different levels of images have appeared to us based on their size, such as the single image that is embodied in one verse and is linked to one sense, the partial image that is embodied in a number of verses and is linked to a number of senses, then the total image that is embodied in the entire text and a number of senses are involved in it. It represents a long scene or a number of scenes or artistic paintings that give us a general picture of the poet’s vision of existence. The visual image occupied first place despite the poet being blind, and we attributed this to his frequent contemplations, his reliance on mental images born of fertile imagination, and the transformation of auditory images into visual images to deny the handicap of blindness and demonstrate his superiority over the sighted.